Coarctation of the aorta: an evaluation of surgical techniques. - Nozar, José V; Galíndez, Eduardo M; Neirotti, Rodolfo; Kreutzer, Guillermo (Cirugía del Uruguay, 1976)
Since 1961, 187 patients were operated upon because of a coarctation of the descending thoracic aorta. Fifty three of these patients were Jess than one year o!d; and 86 % had associated cardiac. iesions. Two different types of surgical techniques were used: resection and end-to-end anastomosis (79 cases) an angioplasty in, 99 cases. The most common associated defects found in the small infant group were patent ductus arteriosus or ventricular septal defect. Surgical treatment was indicated in this group, when medica] treatment was found incapable of reducing cardiac failure. In the older children group, the most frequent associated Jesions were: obstruction to the Jeft ventricular outflow tract ( aortic valvular stenoses or subaortic stenoses). Indications as which of both lesions have to be treated first is decided according to which has the. most important gradient. Patch graft angioplasty is considered to be the best operative procedure for coarctation in small infants and for treatment of recoarctation of the aorta. We think resection and end-tq-end anastomosis still has a place in the treatment of coarctation specially in these favourable cases with a short coarted segments. In our experience the best age for correction of this congenital malformation in assymptomatic patients is around four years of age.